2018
DOI: 10.1002/ecy.2155
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of specialist and generalist herbivores on resistance evolution in invasive plants

Abstract: Invasive alien plants are likely to be released from specialist herbivores and at the same time encounter biotic resistance from resident generalist herbivores in their new ranges. The Shifting Defense hypothesis predicts that this will result in evolution of decreased defense against specialist herbivores and increased defense against generalist herbivores. To test this, we performed a comprehensive meta-analysis of 61 common garden studies that provide data on resistance and/or tolerance for both introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 73 publications
7
59
1
Order By: Relevance
“…In addition, the performance of alien and native species in the test phase did not change with diversity and relative abundance of fungal pathogens in the soil. The lack of evidence for enemy release contrasts with the findings of meta-analyses that found that enemy release contributed to plant invasion 59,60 . This discrepancy could be explained by the fact that the studies included in the meta-analyses mainly focused on aboveground enemies and on herbivores.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, the performance of alien and native species in the test phase did not change with diversity and relative abundance of fungal pathogens in the soil. The lack of evidence for enemy release contrasts with the findings of meta-analyses that found that enemy release contributed to plant invasion 59,60 . This discrepancy could be explained by the fact that the studies included in the meta-analyses mainly focused on aboveground enemies and on herbivores.…”
Section: Discussioncontrasting
confidence: 76%
“…Given that invasive plant species often grow faster than native species (van Kleunen et al ), greater compensatory growth or tolerance might be expected for the former. Indeed, a meta‐analysis by Zhang et al () found that invasive plant species were more tolerant to generalist herbivores than native plant species, however no differences in tolerance to specialist herbivores were observed. Thus, in addition to escape from coadapted herbivores in their native range and greater resistance to herbivores in their introduced range, plant invasion success may also be attributed to greater tolerance of generalist herbivores (Zhang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a meta‐analysis by Zhang et al () found that invasive plant species were more tolerant to generalist herbivores than native plant species, however no differences in tolerance to specialist herbivores were observed. Thus, in addition to escape from coadapted herbivores in their native range and greater resistance to herbivores in their introduced range, plant invasion success may also be attributed to greater tolerance of generalist herbivores (Zhang et al ). However, the relative contribution of each factor to invasion success is poorly understood and more studies are needed that examine different defense mechanisms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptability of invasive species is surprising, since many non‐native species go through genetic bottlenecks during introduction, which is likely to reduce genetic variation (Dlugosch & Parker, ; Hollingsworth & Bailey, ; Schrey et al, ; Zhang, Zhang, & Barrett, ). Nevertheless, there is evidence from comparisons between native and introduced populations that some invasive species have rapidly adapted to new environments (Joshi & Vrieling, ; Zhang et al, ). Moreover, common‐garden studies revealed that trait expression of naturalized non‐native plants often appears to follow altitudinal, climatic, or latitudinal clines (Agrawal et al, ; Alexander, Kleunen, Ghezzi, & Edwards, ; Bhattarai et al, ; Kollmann & Bañuelos, ; Weber & Schmid, ; but see, e.g., Colautti & Lau, ; Datta, Kühn, Ahmad, Michalski, & Auge, ; Ebeling, Stöcklin, Hensen, & Auge, ).…”
Section: Introductionmentioning
confidence: 99%